High-quality electromagnetically-induced absorption resonances in a buffer-gas-filled vapour cell. (3rd January 2018) - Brazhnikov, D V; Ignatovich, S M; Vishnyakov, V I; Skvortsov, M N; Andreeva, Ch; Entin, V M; Ryabtsev, I I
Abstract: Magneto-optical subnatural-linewidth resonances of electromagnetically-induced absorption (EIA) in an alkali vapour cell have been experimentally studied. The observation configuration includes using two counter-propagating pumps and probe light waves with mutually orthogonal linear polarizations, exciting an open optical transition in the 87 Rb D 1 line in the presence of argon buffer gas. The EIA signals registered in a probe-wave transmission reach an unprecedented contrast of about 135% with respect to the wide 'Doppler' absorption pedestal and 29% with respect to the level of background transmission signal. These contrast values correspond to a relatively small resonance full width at half maximum of about 7.2 mG (5.2 kHz). The width of the narrowest EIA resonance observed is about 2.1 mG (1.5 kHz). To our knowledge, such a large relative contrast at the kHz-width is the record result for EIA resonances. In general, the work has experimentally proved that the magneto-optical scheme used has very good prospects for various quantum technologies (quantum sensors of weak magnetic fields, optical switches and other photonic elements).